An investigation into functional electrical stimulation (FES) - induced fatique phenomena using electrical pulses - Jannatul Naeem (Kulliyyah of Engineering, International Islamic University Malaysia, 2014)
The pathway of the brain signals to the nerve and muscle which induce muscle contractions for all kind of voluntary and involuntary physiological movements may be interrupted due to accidents or diseases affecting the spinal cord. The Functional Electrical Stimulation (FES) system which uses short duration electrical pulses has been widely used as part of the rehabilitation program in hospitals to artificially stimulate physical movement to expedite the recovering process among patients. While the use of FES system has shown positive outcomes among patients, the FES system face one main drawback i.e. the muscle fatigue phenomenon. Thus, this research work investigates and analyses the muscle fatigue phenomenon with respect to the FES stimulator parameters. Most of the modern FES stimulator uses monophasic and biphasic square wave signals. In this research, we have developed a transformerless FES stimulator that produces the square wave and the exponential waveform to observe and analyze the effect of different waveforms on muscle fatigue. Besides that, other parameters such as the current intensity (50 mA, 70 mA and 100 mA), the duty cycle (25% and 50%) and the frequency (1 Hz, 5 Hz, 10 Hz and 15 Hz) have also been considered in this work. The experiments were conducted on five healthy volunteers. Our findings show that the current intensity has a direct effect on the strength of the muscle contraction. On top of that, our results show that the muscle fatigue is also directly proportional to muscle frequency as well as to the duty cycle. In all of the experiments, the square wave with the 50% duty cycle produced highest muscle force but at a faster muscle fatigue rate when compared with the 25% duty cycle square wave and the exponential waveform. Interestingly, it is observed that the exponential waveform has recorded to have the slowest muscle fatigue time which means that a longer stimulation time can be applied when using the exponential waveform in an FES system